Rudolph the red-nosed reindeer : Rudolph helps out. (Penguin Putman Books : Schlastic, Inc., 2001)
Rudolph helps Mrs. Claus, the elves, Clarice and Santa get ready for Christmas.
Cover title.
On board pages.
Keywords: Rudolph the Red-nosed Reindeer -- (Fictitious character); Christmas stories; Board books